Covalent antithrombin-heparin effect on thrombin-thrombomodulin and activated protein C reaction with factor V/Va - Walderveen, Maria Christina Van; Berry, Leslie Roy; Atkinson, Helen Mary; Chan, Anthony Kam Chuen (Thrombosis and Haemostasis, 2010)
Thrombomodulin (TM), which variably contains a chondroitin sulfate (±CS), forms an anticoagulant complex with thrombin (IIa). IIaTM(±CS) converts protein C (PC) into activated PC (APC), which then inactivates activated factors V (FVa) and VIII (FVIIIa). This reduces prothrombinase and tenase complexes that generate IIa. Heparin (H) increases the rate of IIa-TM inhibition by antithrombin (AT) and enhances FV cleavage by APC. Our novel covalent AT-H (ATH) product, has superior anticoagulant activity compared to AT + unfractionated H (UFH). We studied mechanisms by which ATH versus AT + UFH inhibits IIaTM(±CS), and ATH influences on APC cleavage of FV/FVa compared to UFH. Findings would determine how these reactions moderate ATH’s overall effects as an anticoagulant. Discontinuous second order rate inhibition assays of IIa-TM(±CS) inhibition by AT + UFH or ATH were performed in presence or absence of human umbilical vein endothelial cells (HUVECs). FV/FVa cleavage by APC in the presence of UFH or ATH was analysed by Western blots. ATH increased IIa-TM(±CS) inhibition to a greater degree than AT + UFH, both on plastic and HUVEC surfaces. Unlike UFH, ATH did not accelerate FV cleavage by APC, but ATH did enhance FVa cleavage relative to UFH. Increased IIa-TM inhibition by ATH downregulates PC activation. However, ATH does accelerate downstream inactivation of FVa, which increases its potency for IIa generation inhibition compared to UFH. This trend holds true in the presence of APC’s cofactor, protein S. Overall, ATH may have a balanced function towards inhibiting or accelerating PC pathway activities.
Keywords: Antithrombin-heparin complex; thrombomodulin; factor V/Va; anticoagulant; heparin